KEPEMILIKAN BLOCKHOLDER, INVESTMENT OPPORTUNITY SET, RASIO LIKUIDITAS, DAN NILAI PERUSAHAAN - Yuliani Yuliani; Muizuddin Muizuddin (Jurnal Keuangan dan Perbankan, 2014)
This research aimed to measure and to find empirical evidence, blockholder ownership toward firm value, therole of Investment Opportunity Set (IOS) as mediating effect of blockholder ownership on firm value and roleof liquidity ratio as moderating effect of IOS on firm value. The research was conducted at manufacturingcompanies listed in Indonesia Stock Exchange in 2008-2012 period. This research used purposive sampling,and the units of analysis were 120 observations. Data analysis used was Structural Equation Modeling (SEM).The result showed that blockholder ownership did not have significant effect to firm value. IOS as full mediationhad an effect on blokcholder ownership toward firm value and liquidity ratio as quite moderation instrengthening the effect of IOS to firm value.